Scroll, Discover, Visit: Potential Of Tiktok Media Platform In Boosting Indonesian Domestic Ecotourism And Nature Conservation - Nurbaiti, Hafiza Rizki (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
The potential of social media to promote ecotourism products and services, and nature conservation through engaging content, needs thorough exploration. This research focuses on TikTok social media platform, which has seen a surge in tourism-related content, particularly linked to Indonesian domestic tourism. As awareness of domestic tourism grows among Indonesians, the use of hashtags to highlight local attractions has become prevalent. This study aims to investigate TikTok's efficacy as a marketing tool for promoting domestic tourism in Indonesia, utilizing the hashtag (#) feature. The frequency of likes, comments, and shares of 50 videos (5 videos from each of 10 popular hashtags) were analyzed. Additionally, the videos against the 7 dimensions of tourism product qualitywere further analyzed. The cumulative engagement metrics for these TikTok videos included 14.9 million likes, 213.2 thousand comments, and 580.9 thousand shares. Despite more than half of the videos falling short of all seven tourism product quality dimensions, they still managed to attract millions of views and significant engagement. The findings suggest that TikTok holds considerable potential as an effective marketing tool for tourism industry, especially in enhancing visibility and engagement for Indonesian domestic ecotourism and nature conservation efforts. Future research should further explore the impact of content quality on long-term tourism sustainability and conservation awareness.